Single nucleotide polymorphism of prolactin gene exon two in ducks of Pekin, Mojosari and Pekin Mojosari crossbred - Irma .; Cece Sumantri; Triana Susanti (Indonesian Center for Animal Research and Development (ICARD), 2014)
Prolactin gene plays crucial role in the reproduction and egg production of birds. The objectives of this study were to characterize single nucleotide polymorphism in partial intron and coding region of duck prolactin gene. Blood samples were collected from 168 ducks consisted of 19 Pekin, 36 Mojosari, and 113 of their crossbreds collected from Indonesian Research Institute for Animal Production (IRIAP). Primer pairs for the coding regions in prolactin gene were self designed based on the duck genomic sequence database (GeneBank: AB158611.1). PCR products based on DNA of prolactin gene exon two was amplified approximately 400 bp. There is one base insertion of Adenin at the position of 2001 bp intron two region of duck prolactin. Homology test based on BLAST method indicated 99% identity with duck refference (Code Access GeneBank: AB158611.1). Adenin composition in all of duck samples was higher than refference. Triplet hydrogen bonds between Guanine and Cytosin pairs was higher than those at duplet hydrogen bonds between Adenine and Thymine. All duck samples were homozigous and monomorphyc.